Desain Sistem Pengisian Baterai Berbasis Solar Sel Menggunakan Regulator MPPT - Insani, Ridho Syahrul; Zakri, Azriyenni Azhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
One alternative energy source that can be used is energy derived from sunlight. One important aspect that aims to improve the efficiency of solar cells is the Maximum Power Point Tracker (MPPT) on solar cells. The MPPT system aims to find a solar cell working point where solar cells are able to produce maximum power and detect solar cells work at that optimal point. The MPPT algorithm is the main part of the MPPT system, one of the MPPT algorithm is the Incremental Conductance Method (ICM). The ICM algorithm in this study is the MPPT method used by solar cells that detect the optimum conditions in various conditions the input values change in of solar cells. The ICM algorithm on a 100 Watt solar cell system is used for battery charging, the battery used is a lead-acid type with a nominal voltage of 12 Volts, a capacity of 6.5 Ah produces a maximum output power of 87.37 Watts. The increase in battery State of Charge (SOC) of 10% and 90%. Setting a battery SOC of 10% with 0.1% increase in battery SOC occurs at 2.7 seconds in simulation time or 27 minutes of real test time and battery SOC with a setting of 90% SOC increase in 0, 1% battery SOC occurred at 1.8 seconds at simulation time or 18 minutes real test time. Keywords:ICM Algorithm, Battery, Buck boost converter, MPPT, Solar cell